Full-day School Learning Planning at the Integrated Islamic Elementary School Sahabat Qur'an, Central Bangka Regency - Judaini, Judaini; Fitria, Happy; Eddy, Syaiful (Jurnal Sustainable, 2024)
Learning planning is a general description of a teacher's steps to effectively and efficiently achieve the goals. This research aims to determine and analyse full-day school learning planning at the Sahabat Qur'an Integrated Islamic Elementary School, Central Bangka Regency. The research is descriptive qualitative research with data collection techniques in the form of interviews, field observations and document studies. The research results show that full-day school learning planning at the Sahabat Qur'an Integrated Islamic Elementary School is implemented for all subjects, including general and typical lessons at SDIT Sahabat Qur'an. Full-day learning planning at the Sahabat Qur'an Integrated Islamic Elementary School has been carried out simultaneously and systematically by each teacher in general subjects. However, in particular issues, some teachers still need to be more systematic in their learning planning.